Reflection of Pancasila Values in the Television News Show “Apa Kabar Indonesia Pagi” on TvOne - Ravinska Vigna Viori; Adelia Irfana Putri; Edi Priyono (Communigate, 2025)
This study analyses the reflection of Pancasila values in the news program “Apa Kabar Indonesia Pagi” on TvOne. Using the critical discourse analysis method, it evaluates how news completeness, narrative delivery, and perspectives align with Pancasila principles, such as justice, humanity, and unity. The findings reveal that the analysed news effectively incorporates these values through empathetic, neutral, and in-depth reporting. The study also identifies challenges in implementing Pancasila values in the digital era, including the spread of misinformation and social polarization, while proposing solutions such as digital literacy and Pancasila-based character education. The conclusion emphasizes that media, through ethical information dissemination, plays a strategic role in reinforcing national values.